Perawatan Paliatif Berbasis Family Centered Nursing untuk Mempertahankan Status Gizi Penderita Penyakit Ginjal Kronik dengan Hemodialisis - Faridah, Virgianti Nur; Pramestirini, Rizky Asta; Zuliastri, Nofi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Chronic kidney disease patients on hemodialysis for a long time often experience nutritional status problems due to lack of nutritional intake and protein loss during hemodialysis, so special care is needed. This study aimed to analyze the effect of family centered nursing-based palliative care on the nutritional status of chronic kidney disease patients on hemodialysis. The design of this research was post-test only with control group. This study involved 30 patients for each group, selected by purposive sampling technique. Data on nutritional status were collected using the SGA questionnaire and analyzed using the Chi-square test. Based on the results of the analysis, the p-value = 0.030 was obtained, so it was interpreted that there was a difference in nutritional status between the two groups, with a higher score obtained in the group given palliative care based on family centered nursing. Based on these results, it was concluded that palliative care based on family centered nursing was effective in maintaining the nutritional status of patients with chronic kidney disease undergoing hemodialysis.Keywords: chronic kidney disease; hemodialysis; palliative care; family centered nursing; nutritional status ABSTRAK Pasien penyakit ginjal kronik dengan hemodialisis dalam waktu lama sering mengalami masalah status gizi akubat kurangnya asupan nutrisi dan kehilangan protein saat hemodialisis, sehingga diperlukan perawatan khusus. Penelitian ini bertujuan untuk menganalisis pengaruh perawatan paliatif berbasis family centered nursing terhadap status gizi pasien penyakit ginjal kronik dengan hemodialisis. Desain penelitian ini adalah post-test only with control group. Studi ini melibatkan 30 pasien untuk masing-masing kelompok, yang dipilih dengan teknik purposive sampling. Data tentang status gizi dikumpulkan menggunakan kuesioner SGA dan dianalisis menggunakan uji Chi-square. Berdasarkan hasil analisis didapatkan nilai p = 0,030, sehingga diinterpretasikan bahwa ada perbedaan status gizi di antara kedua kelompok, dengan skor yang lebih tinggi didapatkan pada kelompok yang diberikan perawatan paliatif berbasis family centered nursing. Berdasarkan hasil tersebut disimpulkan bahwa perawatan paliatif berbasis family centered nursing efektif untuk menjaga status gizi pasien dengan penyakit ginjal kronik yang menjalani hemodialisis.Kata kunci: penyakit ginjal kronik; hemodialisis; perawatan paliatif; family centered nursing; status gizi